AN ANALYTICAL STUDY ON PHYSICAL EDUCATION TEACHERS’ ATTITUDES TOWARDS THE APPLICATION OF INTERACTIVE TEACHING METHODS IN SCHOOLS - Hussein Jassim Jawad (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. The integration of interactive teaching methods in physical education is considered essential for enhancing students’ learning experiences and engagement. However, teachers’ attitudes and their level of application remain key factors influencing the success of such approaches. Objectives. This study aimed to analyze the attitudes of physical education teachers towards the use of interactive teaching methods, assess their knowledge of these approaches, examine the extent of their practical application during classes, and identify factors that facilitate their implementation and impact on student learning. Method. The research employed a descriptive-analytical design using a structured questionnaire administered to a sample of 100 male and female physical education teachers in Diwaniyah schools. The instrument covered five dimensions: general attitudes, knowledge of interactive methods, level of actual application, factors enhancing application, and the perceived impact on students’ learning. Results. The findings revealed that physical education teachers hold positive attitudes toward interactive teaching methods; however, their actual classroom application remains limited. Key enablers include administrative support, continuous professional development, and the availability of adequate educational resources. Furthermore, the study found that applying interactive methods positively influences students’ academic performance and engagement. Conclusion. In conclusion, the study highlights the need to expand specialized training programs, improve classroom facilities, strengthen administrative support, and provide both material and moral incentives to encourage teachers’ adoption of interactive approaches. The study contributes to the field by offering empirical evidence on the gap between attitudes and practices and by proposing strategies to foster effective implementation of interactive teaching methods in physical education.